Linoleic acid metabolite 13-Hydroxyoctadecadienoic acid as a biphasic ferroptosis modulator in granulosa cells: multi-omics analysis of ovine atretic follicles - Song, Yukun; Hai, Erhan; He, Lixia; Zhang, Ning; Zhang, Nan; Wang, Junlan; Sun, Yupeng; Zeng, Dengke; Zhang, Jiaxin (Frontiers in Cell and Developmental Biology, 2025)
Introduction13-Hydroxyoctadecadienoic acid (13(S)-HODE) is a bioactive lipid derived from linoleic acid, it plays prominent roles in cellular processes such as lipid metabolism, oxidative stress, and apoptosis. Follicular atresia is a complex physiological process involving multiple forms of cell death. Ferroptosis, an iron-dependent form of programmed cell death, has been less studied in the context of follicular atresia.MethodsTo investigate the association between ovine follicular atresia and ferroptosis, we performed transcriptomic and metabolomic analyses of healthy and atretic sheep follicles. Notably, sheep follicular granulosa cells were treated with different doses of 13(S)-HODE. Cell viability, lipid peroxidation levels, ferroptosis-related markers, and ferroptosis-related genes were measured.ResultsThe metabolomic analysis identified 87 and 48 differentially expressed metabolites in healthy and atretic follicles, respectively. Functional enrichment of atretic follicle fluid highlighted pathways related to linoleic acid and purine metabolism. Transcriptomic analysis revealed 250 highly expressed genes in ovarian granulosa cells of atretic follicles. Enrichment analysis indicated that these differentially expressed genes were associated with fatty acid metabolism and ferroptosis. Integration of multi-omics data demonstrated the occurrence of ferroptosis in atretic follicles, where 13(S)-HODE drives granulosa cell ferroptosis via the linoleic acid metabolism pathway; this effect was not dose-dependent. Mechanistic studies showed that low-dose 13(S)-HODE counteracts ferroptosis by promoting glutathione peroxidase 4-mediated lipid peroxidation reduction and increasing glutathione levels.DiscussionIn contrast, high-dose 13(S)-HODE induces labile iron accumulation through activation of transferrin receptor and ferritin heavy chain 1, enhancing ferroptosis sensitivity in granulosa cells. These findings provide insights into the molecular mechanisms regulating follicle development and offer potential therapeutic targets for enhanced follicular development and improved reproductive outcomes.